The Fundamental of Ethics, en: A. Masferrer, "Criminal Law and Morality in the Age of Consent". Interdisciplinary Perspectives, pp. 171-189 - Carpintero Benítez, Francisco (Revista de Derecho, 2024)
A doctrine concerning the foundations of ethics must be regarded as a reflection upon Natural Law. It is indeed possible to discuss principles or values deemed to hold particular significance, often referred to as superior or democratic values. Nonetheless, such values do not constitute a solid foundation, as it is well established that numerous values of this nature have experienced a decline in relevance in recent years. For instance, the United Nations (UN) has recently urged States to adopt measures ensuring that religious denominations comply with LGTBI legislation. The doctrinal basis of Natural Law was formulated during the 13th and 14th centuries, initially by Thomas Aquinas and subsequently by John Duns Scotus. Nominalist philosophers, such as Scotus, conceived realities akin to contemporary values, asserting that the moral principles that should inform the law are mental constructs inherently present in human reason. Francisco Suárez, adhering to nominalist principles, introduced this theory into the Modern Era in the early 17th century. The explanation proffered by Thomas Aquinas did not achieve widespread acceptance, possibly due to a deficiency in comprehensive study, and eventually fell into obscurity. In the culmination of this historical process, the notion of Natural Law as an eternal and immutable ordinance prevailed, on the basis that, as Suárez elucidated, "God cannot contradict Himself." Shortly thereafter, adherents emphasized, albeit with limited nuance, the strictly metaphysical foundation of Natural Law.